Polymer Dielectrics for 3D‐Printed RF Devices in the Ka Band. Issue 2 (6th May 2016) - Lis, Michael; Plaut, Maxwell; Zai, Andrew; Cipolle, David; Russo, John; Lewis, Jennifer; Fedynyshyn, Theodore
Abstract : Direct‐write printing allows the fabrication of centimeter‐wave radio devices. Most polymer dielectric polymer materials become lossy at frequencies above 10 GHz. Presented here is a printable dielectric material with low loss in the K a band (26.5–40 GHz). This process allows the fabrication of resonator filter devices and a radio antenna.